Deformation modes during room temperature tension of fine-grained pure magnesium. (March 2021) - Zeng, Zhuoran; Zhou, Mengran; Lynch, Peter; Mompiou, Frédéric; Gu, Qinfen; Esmaily, Mohsen; Yan, Yuanming; Qiu, Yao; Xu, Shiwei; Fujii, Hidetoshi; Davies, Chris; Nie, Jian-Feng; et al.
Abstract: Extruded polycrystalline pure magnesium (Mg) with fine grain size ( 1.2 µm) exhibits ductility of over 100% at room temperature, in spite of the presence of a strong basal texture. In this study, a set of complementary in-situ characterisation techniques over multiple-length scales were utilised to reveal the deformation modes enabling such ductility. Synchrotron X-ray diffraction results show that the elastic lattice strain of fine-grained sample for tensile elongation up to 55% is 3–10 times lower than that in the coarse-grained sample, indicating the absence of significant strain accumulation inside fine grains and potential inter-granular deformation in bulk. In-situ scanning electron microscopy validates the predominant operation of the inter-granular deformation, and it further reveals that the inter-granular deformation occurs by the relative sliding between groups of grains having similar orientations. The deformation resulting from such sliding is substantial, and it is accommodated by the rotation of grains located between slid grouped grains, from hard to softer orientations to allowing dislocation slip to readily occur. The accommodating mode of dislocation slip is further supported by in-situ transmission electron microscopy observations. Dislocations glide readily to, and annihilate at, grain boundaries. The observations and direct evidences presented herein suggest that the major deformation mode is sliding between grouped grains that is accommodated by grain rotation and dislocation slip, in contrast to dislocation slip in coarse-grained Mg. The coordinated deformation processes postpone the occurrence of localised stress concentration and greatly increases the ductility of pure Mg at room temperature. Graphical abstract: Image, graphical abstract